Analysis of Barriers to the Use of Health Information Systems for Tuberculosis Patients at the Parongpong Community Health Center, West Bandung Regency, Indonesia - Warna, Mawar Puspa; Indasah, Indasah (Asian Journal of Health and Applied Sciences, 2023)
Based on the rules from the government contained in the Regulation of the Minister of Health of the Republic of Indonesia Number 31 of 2019, the Public Health Center information system can be implemented electronically so that the data obtained can be stored safely. An electronic health center information system must have an application, an internet, and a local network (LAN). This can also support Health Promotion activities through electronic media and online reporting to the Minister of Health of the Republic of Indonesia. This research aims to apply innovative health education to the problem of low Tuberculosis patient visits. This is done by analyzing a fishbone diagram and determining priority solutions to problems that have resulted in no real follow-up plans (RTL) so that targets have not been met and there has been no evaluation action at the Parongpong Health Center. This activity is carried out in several stages, namely 1) problem analysis with fishbone, 2) USG (urgency, seriousness, growth), and 3) SWOT analysis. Furthermore, counseling was carried out to all people in the Parongpong sub-district. The results obtained from calculating the score using the SWOT analysis are to make regulations on procedures and standard operating procedures (SOP) for the use of the Tuberculosis Information System (SITB) to optimize health information management at the Parongpong Health Center, West Bandung Regency, Indonesia.